Length of Human Vermiform Appendix in Bangladeshi People - Rahman, Md Mahbubur; Khalil, Mohsin; Khalil, Mansur; Hussain, Anwar; Rahman, Habibur Rahman; Mannan, Sabina; Sultana, Seheli Zannat; Ahamed, M Shibbir (Journal of Bangladesh Society of Physiologist, 2008)
The study was done to find out the length of human vermiform appendix in Bangladeshi people to magnify the knowledge regarding the diverse length of human vermiform appendix in our population. A total 100 vermiform appendix were measured with different age and sex during routine postmortem examination in the autopsy laboratory of forensic medicine department of Mymensingh Medical College. This cross sectional study was done by convenient sampling technique. For convenience of differentiating the length of vermiform appendix in relation to different age and sex, findings were classified in four groups (up to 20 years, 21 to 35 years, 36 to 55 years and 56 to 70 years). Length of vermiform appendix was 2.6 cm to 14 cm. Mean length was 7.9 cm in female and 7.56 cm in male. The highest mean length of vermiform appendix in group A was 9.17 cm and lowest was 5.93 cm in group D. Key words: Human Vermiform Appendix; Length; Bangladesh DOI:10.3329/jbsp.v2i0.977 J Bangladesh Soc Physiol. 2007 Dec;(2): 13-16